1977
DOI: 10.1093/jn/107.1.42
|View full text |Cite
|
Sign up to set email alerts
|

Physiological Responses of Human Adults to Foods Containing Phosphate Additives

Abstract: An experiment was conducted to assess the physiological effects of a diet rich in foods cotaining phosphate additives. During a 4-week control period, eight adults were fed a balanced diet free of phosphate additives providing approximately 95 g protein 0.7 g Ca and 1.0 g P per day. During a subsequent 4-week period, food items containing phosphate additives were substituted for counterpart items devoid of added phosphates. This diet contained 0.7 g Ca and 2.1 g P per day. The introduction of foods containing … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
112
0
1

Year Published

1989
1989
2018
2018

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 193 publications
(119 citation statements)
references
References 10 publications
6
112
0
1
Order By: Relevance
“…The introduction of a diet rich in phosphorus was associated with intestinal distress, soft stools or mild diarrhoea in young women. This physiological response to phosphorus supplementation in the present study was in agreement with that observed by Bell et al (1977). In their investigation eight human subjects ®rst received a control diet containing 1 g P per day for 4 weeks; this was followed by 4 further weeks with a high-phosphorus diet providing approximately 2.1 g of phosphorus in the form of sodium polyphosphates.…”
Section: Discussionsupporting
confidence: 92%
“…The introduction of a diet rich in phosphorus was associated with intestinal distress, soft stools or mild diarrhoea in young women. This physiological response to phosphorus supplementation in the present study was in agreement with that observed by Bell et al (1977). In their investigation eight human subjects ®rst received a control diet containing 1 g P per day for 4 weeks; this was followed by 4 further weeks with a high-phosphorus diet providing approximately 2.1 g of phosphorus in the form of sodium polyphosphates.…”
Section: Discussionsupporting
confidence: 92%
“…Then, as now, many believed that the phosphorus content of the American diet was increasing as a result of the growing availability of and preference for processed foods and the widespread use of phosphate additives by food processors (4)(5)(6). Recently, this interest has been rekindled, sparked by new knowledge about the tight endocrine regulation that maintains phosphorus balance and newly gained understanding of how this balance can be disrupted by acute or prolonged excessive intakes of phosphorus (7).…”
Section: Introductionmentioning
confidence: 99%
“…It increases parathyroid hormone (PTH) secretion (1,2), which causes an increase in bone resorption and a decrease in bone mineral density (BMD) (3)(4)(5). Our previous study demonstrated that elevated PTH secretion from a high-P diet increases mRNA expression of the receptor activator of NF-kB ligand (RANKL), a mediator of osteoclastic bone resorption, resulting in increased osteoclastic bone resorption (4).…”
mentioning
confidence: 99%